2022
DOI: 10.1177/24730114221103263
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Body Mass Index and Outcomes of Arthroscopic Treatment for Osteochondral Lesions of the Talus

Abstract: Background: Osteochondral lesions of the talus (OLTs) are a common condition found in patients with chronic ankle pain after previous ankle sprains. Surgical management is indicated after conservative management has failed. Hypothesis/Purpose: This study evaluates the influence of body mass index (BMI) on the early clinical outcomes of arthroscopic debridement and microfracture of OLTs. Methods: A total of 252 patients with symptomatic OLTs who failed conservative management underwent arthroscopic debridement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
2
4
1
Order By: Relevance
“…The BMI of patients with good/excellent joints was significantly lower than that of patients with fair and poor joints, and our analysis was based on the following two reasons: Firstly, obesity has negative physiologic and psychological impacts on patients' postoperative quality of life and affects their postoperative recovery. Secondly, obese patients have a poor prognosis for the development of degenerative joint disease, consistent with previous studies (43,44). Finally, obesity-associated behavior such as functional limitations, constant dieting, and mental stress from their body image and poor self-esteem, coupled with social stigma, all play a strong role linking obesity with depression (45).…”
Section: Chuckpaiwong Et Al (11) Reported Good Functional Results Ofsupporting
confidence: 86%
See 1 more Smart Citation
“…The BMI of patients with good/excellent joints was significantly lower than that of patients with fair and poor joints, and our analysis was based on the following two reasons: Firstly, obesity has negative physiologic and psychological impacts on patients' postoperative quality of life and affects their postoperative recovery. Secondly, obese patients have a poor prognosis for the development of degenerative joint disease, consistent with previous studies (43,44). Finally, obesity-associated behavior such as functional limitations, constant dieting, and mental stress from their body image and poor self-esteem, coupled with social stigma, all play a strong role linking obesity with depression (45).…”
Section: Chuckpaiwong Et Al (11) Reported Good Functional Results Ofsupporting
confidence: 86%
“…Finally, obesity-associated behavior such as functional limitations, constant dieting, and mental stress from their body image and poor self-esteem, coupled with social stigma, all play a strong role linking obesity with depression (45). In Group B, we concluded that an elevated BMI did not adversely affect pain and function, and a high proportion of patients reported greater postoperative satisfaction and achievement, similar to other studies (44). Instead, patients should be encouraged to normalize their BMI in view of the negative impact on their quality of life and the physical limitations associated with a raised BMI.…”
Section: Chuckpaiwong Et Al (11) Reported Good Functional Results Ofsupporting
confidence: 85%
“… a Significantly different from osteo(chondral) autograft transplantation therapies ( Q = 7.55, P = 0.0060) and metal implants ( Q = 5.27, P = 0.0217). 43,52,59,61 -63,66,81,92,93,109,113,117,121,123,125,131,135,141,143,146,149,150,153,158,164,165,167,168,171,173,176,177,179 -183,187,190,192,195 -200,202,204 -206 b Significantly different from metal implants ( Q = 3.86, P = 0.0493). 11,42,53,56,59,116,118,137,170,…”
Section: Resultsmentioning
confidence: 99%
“…The effect of BMI on clinical outcomes remains debated. A recent study by Koh et al 27 reported that a BMI of ≥25 kg/m 2 was not associated with decreased outcomes at 2 years of follow-up in 252 patients who underwent arthroscopic BMS. Indeed, the aforementioned authors found that a higher BMI appeared to be weakly associated with improved outcomes.…”
Section: Discussionmentioning
confidence: 96%